KAFĀ’AH IN THE AHMADIYYA MARRIAGE: HOMOGAMOUS- HETEROGAMY AND SECT PRESERVATION - Hasan, Ikhwan Fuad; Santoso, Lukman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2019)
Ahmadiyya has a different concept of kafā’ah in marriage compared to several Muslims communities. The majority of Muslim scholars agree the main factor of kafā’ah in marriage is religiosity which is interpreted as theistic and moral, but Ahmadiyya interprets it as religious commonality. As a result, an Ahmadi woman is forbidden to marry a non-Ahmadi man. Meanwhile, an Ahmadi man is allowed to marry a non-Ahmadi woman, even a non-Muslim woman. Any adherent who violates the provision will be removed from the sect as an organizational sanction. Related to the facts, this paper aims to discuss the motivation, strategy, and goal of the provision. It uses a descriptive-analytic approach to analyze kafā’ah provision in Ahmadiyya literature with homogamy and heterogamy concepts. The results of this study show that the provision is motivated by historical and social factors, such as group discrimination, operational prohibitions, physical and non-physical violence. In addition, Ahmadiyya implements a homogamous-heterogamy concept in the provision as a strategy to preserve its teachings and resist its adherents from other religious affiliations. The provision has been preserving the existence of Ahmadiyya from its establishment to the present. Keywords: Ahmdiyya, Kafā’ah, Homogamy, Heterogamy